Preventive Effect of Professional Fluoride Supplements on Enamel Demineralization in Patients Undergoing Fixed Orthodontic Treatment: A Systematic Review and Meta-Analysis - Elham Babadi Oregani; Alireza Jafari; Seyed Masoud Sajedi; Saeed Reza Motamedian (Galenos Yayinevi, 2022)
Objective: The current study aimed to systematically review the randomized clinical trials assessing the preventive effect of professional fluoride interventions on enamel demineralization in patients undergoing fixed orthodontic treatment.Methods: The electronic search was performed in PubMed and Cochrane library in September 2021. No restriction was set on the publication date. Randomized clinical trials assessing the preventive effect of fluoride varnish, gel, mouthwash, and high-fluoride toothpaste on white spot lesions compared to the control group by clinical or radiographic methods in more than 10 patients were included.Results: A total of 7 articles consisting of 1418 participants were included. In 4 articles, fluoride varnish (contained a range of 1000-50 000 ppm fluoride) was applied multiple times (4-20 times) in test groups. Their results indicated that the test groups significantly had lesser new white spot lesions or advanced white spot lesions. One study used fluoride varnish only once at the beginning of treatment and reported no significant difference in white spot lesions compared to the control group. Application of high-fluoride toothpaste as well as fluoride mouthwash, also, showed significantly lower white spot lesions. Three studies were included in the meta-analysis and revealed that the relative risk of white spot lesions was 0.64 (95% CI = 0.40 to 0.89; P < .01) in favor of fluoride varnishConclusion: Multiple applications (4-20 times) of fluoride varnish or daily use of fluoride mouthwash or high-fluoride toothpaste seem to reduce white spot lesions in patients undergoing orthodontic treatment. However, single use of fluoride varnish was not effective. Further research is needed to establish the required number of fluoride applications for the prevention of white spot lesions during orthodontic treatment.